Feeding habits of chironomids (Diptera: Chironomidae) of paramo Chingaza lakes, Colombia. - Caleño Ruiz, Yulibey; Rivera Rondon, Carlos Alberto; Ovalle, Hernando (Revista de Biología Tropical, 2018)
Tropical high mountain lakes show unique environmental conditions where chironomids play an important role in ecosystem functioning. The characteristics of these environments could favor diet overlap and therefore a high interspecific competition. This study described the dietary habits of chironomid genera, identified whether the dietary habits were specialized or generalist, and analyzed the diet overlap in the genera. Chironomidae larvae were collected from four lakes of the Chingaza paramo during the dry season, between April and May of 2 016. The feeding habits of larvae were evaluated by analyzing gut contents following standard methods. Each genus was assigned to trophic guilds (carnivore, detritivore and algivore) and the diet overlap was estimated using the Pinka's index. A total of 1 003 individuals were collected and nine genera were identified. Larvae consumed mainly fine particulate organic matter (FPOM), algae, macrophyte fragments, macroinvertebrates, and animal tissues. FPOM was the main feeding resource of detritivores. The analysis of diets showed a high affinity of each genus for a single trophic guild and most of the genera were generalist in the use of resources. For all lakes, high levels of diet overlap were observed among genera and trophic guilds, mainly among detritivores. Our results suggested that Chironomidae larvae of these lakes presented well differentiated trophic habits, and showed a moderate diet overlap within detritivores and carnivores.